Net Neutrality: Goal, Efficacy, Effectiveness and Efficiency (Law, State and Telecommunications Review, 2015)
Purpose ”“ This article aims to address the role of net neutrality on the Internet network structure’s scarcity.Methodology/approach/design ”“ It analyses cases of Internet service’s success and failure to illustrate a few points of what is claimed by net neutrality advocates. In addition, it draws a parallel of the difficulties faced by content providers, but not by network providers, and how strategies of the latter can simultaneously violate the net neutrality, harm the former and cause negative impact on their strategies, and harm users. Concerning this issue, this study makes a comparison of the current regulatory environment in Brazil and in the United States and uses convergence and intersection between Game Theory, transaction costs of Coase Theorem, Public Interest Theory and the design of an efficient and equitable regulatory system to analyze the purpose of the players.Findings ”“ This article suggests parameters of goal, efficacy, effectiveness and efficiency as means to prevent violations of net neutrality in issues involving internet users.Practical implications ”“ It helps evaluate relationships that have the potential to violate the principle of net neutrality.